(3ejKGb hdi GdReGfs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi ehdGfG GdMGce GdCMO GdaQO GdUeO GdefRg Yf GdCRhGL hGdYOO EbQGQkG ChLHg Ydi faSg hGTgO Hg Ydi QhMg s
(3BNQgG (B:s
(3cGf ef GdehMOjf GdaGFRjf hcJH ai TgQ cPG hcPG ef SfI cPG hcPG HSja ehdGfG Ld PcQg hTOg SdWGfg hMOg Je s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdJhMjO hGdedd hGdfMds